Heparin-Binding Hemagglutinin Adhesin (HBHA) Is Involved in Intracytosolic Lipid Inclusions Formation in Mycobacteria - Raze, Dominique; Verwaerde, Claudie; Deloison, Gaspard; Werkmeister, Elisabeth; Coupin, Baptiste; Loyens, Marc; Brodin, Priscille; Rouanet, Carine; Locht, Camille (Frontiers in Microbiology, 2018)
The heparin-binding hemagglutinin (HBHA) is an important virulence factor of Mycobacterium tuberculosis. It is a surface-displayed protein that serves as an adhesin for non-phagocytic cells and is involved in extra-pulmonary dissemination of the tubercle bacillus. It is also an important latency antigen useful for the diagnosis of latently M. tuberculosis-infected individuals. Using fluorescence time-lapse microscopy on mycobacteria that produce HBHA-green fluorescent protein chimera we show here that HBHA can be found at two different locations and dynamically alternates between the mycobacterial surface and the interior of the cell, where it participates in the formation of intracytosolic lipid inclusions (ILI). Compared to HBHA-producing mycobacteria, HBHA-deficient mutants contain significantly lower amounts of ILI when grown in vitro or within macrophages, and the sizes of their ILI are significantly smaller. Lipid-binding assays indicate that HBHA is able to specifically bind to phosphatidylinositol and in particular to 4,5 di-phosphorylated phosphatidylinositol, but not to neutral lipids, the main constituents of ILI. HBHA derivatives lacking the C-terminal methylated, lysine-rich repeat region fail to bind to these lipids and these derivatives also fail to complement the phenotype of HBHA-deficient mutants. These studies indicate that HBHA is a moonlighting protein that serves several functions depending on its location. When surface exposed, HBHA serves as an adhesin, and when intracellularly localized, it participates in the generation of ILI, possibly as a cargo to transport phospholipids from the plasmic membrane to the ILI in the process of being formed.